An in vitro method for nephrotoxicity evaluation using HK-2 human kidney epithelial cells combined with biomarkers of nephrotoxicity. Issue 6 (24th August 2018) - Qiu, Xuan; Zhou, Xiaobing; Miao, Yufa; Li, Bo
Abstract : The HK-2 cell model based on clusterin, osteopontin, CysC and KIM-1 would allow the prediction of nephrotoxicity at early stages. Abstract : The kidney is one of the major target organs for drug-induced toxicity. During drug development, the traditional markers of nephrotoxicity indicate only severe and late damage, which leads to high costs. The new biomarkers are needed for a more sensitive and reliable evaluation of nephrotoxicity, especially for the regulatory accepted and validated in vitro model. We developed an in vitro model based on the HK-2 cell using the biomarkers of nephrotoxicity as endpoints for the evaluation of nephrotoxicity. The predictive performance of the biomarkers including LDH, GGT, KIM-1, clusterin, CysC, NGAL, TIMP-1, GSTπ and osteopontin was evaluated with 22 well characterized compounds. The area under the curve (AUC) values of KIM-1, clusterin, CysC and osteopontin ranged between 0.79 and 0.84. The combination of clusterin, KIM-1 and/or osteopontin improved the AUC value (ranging between 0.88 and 0.95) compared to one biomarker. Taken together, these results suggest that the model based on the HK-2 cell using clusterin, osteopontin, CysC and KIM-1 as endpoints would allow the prediction of nephrotoxicity at early preclinical stages.